PEMODELAN SEKTOR UNGGULAN PROVINSI KALIMANTAN BARAT DENGAN MENGGUNAKAN PRINCIPAL COMPONENT ANALYSIS - Satyahadewi, Neva; Aprizkiyandari, Siti; Radinasari, Nur Ismi (TRANSFORMASI, 2023)
West Kalimantan is the province with the fourth largest area in Indonesia, namely 147,307 square km. West Kalimantan has 12 districts and 2 cities, one of which is Ketapang Regency which covers an area of ​​31,240.74 km2. The research is limited to three leading sectors which have the largest average contribution to GRDP in West Kalimantan Province, namely the agriculture, forestry and fisheries sectors; industrial processing; as well as wholesale and retail trade, and car and motorcycle repair. The focus of this research is aimed at modeling the leading sector for the West Kalimantan economy. The results of the modeling showed multicollinearity so it was continued with the Principal Component Analysis. The results of the analysis with the model show that there is no element of multicollinearity between the dependent variables.